Comparison of Carbapenem-Resistant Klebsiella pneumoniae Strains Causing Intestinal Colonization and Extraintestinal Infections: Clinical, Virulence, and Molecular Epidemiological Characteristics - Wenli Liao (Frontiers Media S.A., 2021)
Carbapenem-resistant Klebsiella pneumonia (CRKP) infections has become a concerning threat. However, knowledge regarding the characteristics of intestinal CRKP isolates is limited. This study aimed to investigate and compare the clinical, virulence and molecular epidemiological characteristics of intestinal colonization and extraintestinal infections CRKP strains. The clinical characteristics were investigated retrospectively. Polymerase chain reaction was used to investigate the capsular serotype, virulence genes and carbapenemase genes. Capsular polysaccharide quantification assay, serum resistance assay, biofilm formation assay, and infection model of Galleria mellonella larvae were performed to compare the virulence and pathogenicity. Besides, multilocus-sequence-typing (MLST) and pulsed-field-gel-electrophoresis (PFGE) were conducted to explore the homology of intestinal CRKP isolates. A total of 54 intestinal CRKP isolates were included. The main capsular serotypes were K14, K64, and K19. C-reactive protein and the proportion of ICU isolation of the infection group were significantly higher than that of the colonization group (P < 0.05). The carrier rates of various virulence genes of CRKP in the infection group were mostly higher than those in the colonization group, wherein the carrier rates of peg-344 and rmpA were significantly different (P < 0.05). There was no significant difference in capsular polysaccharides, antiserum ability, biofilm formation ability between the two group (P > 0.05), but the lethality of the infection group to Galleria mellonella was significantly higher than that of the colonization group (P < 0.05). The MLST categorized the 54 isolates into 13 different sequence types. PFGE revealed that homology among the 54 CRKP strains was <80%. This study suggested that the CRKP strains in the infection group had higher virulence than those in the colonization group. The development of CRKP isolates colonizing in the intestine should be addressed in future clinical surveillance.